Resettlement sebagai Durable Solution: Reorientasi Kebijakan Bangladesh dalam Krisis Pengungsi Rohingnya - Muhammad Aditya Purnomo (HK Publishing, 2025)
The Rohingya refugee crisis has exerted profound socio-economic and environmental pressures on Bangladesh since the first major influx in 1978. With over 600,000 refugees recorded in 2017, Bangladesh has faced acute shortages of clean water and firewood, deteriorating sanitation, and increased labor market competition between refugees and local communities. As a developing country with limited resources and a dense population, Bangladesh struggles to sustain long-term humanitarian commitments. Drawing on the Durable Solutions Framework of UNHCR (2003) and the Commission of the European Communities (2004), this article argues that resettlement offers the most viable and sustainable policy alternative compared to repatriation or local integration. Resettlement to third countries—such as Indonesia and Malaysia—can alleviate domestic resource pressures while promoting equitable global burden-sharing. The study concludes that resettlement should be understood not merely as a humanitarian measure but as a strategic policy instrument balancing Bangladesh’s national interests with international solidarity and shared responsibility in refugee governance. Keywords: Rohingya refugees, Bangladesh, Resettlement, Durable Solution, Refugee Policy Abstrak Krisis pengungsi Rohingya yang melanda Bangladesh sejak 1978 hingga kini telah menciptakan tekanan multidimensional terhadap negara tuan rumah, terutama pada aspek sosial-ekonomi dan sumber daya alam. Lonjakan pengungsi yang mencapai lebih dari 600.000 jiwa pada 2017 menyebabkan kelangkaan sumber daya seperti air bersih dan kayu bakar, penurunan kualitas sanitasi, serta meningkatnya kompetisi tenaga kerja antara pengungsi dan masyarakat lokal. Kondisi ini memperlihatkan keterbatasan kapasitas Bangladesh sebagai negara dengan perekonomian lemah dan populasi tinggi dalam menyediakan perlindungan jangka panjang bagi pengungsi. Berdasarkan kerangka Durable Solution yang dikembangkan oleh UNHCR (2003) dan Komisi Eropa (2004), penelitian ini berargumen bahwa resettlement merupakan opsi paling realistis dan berkelanjutan dibandingkan repatriasi maupun integrasi lokal. Melalui pemukiman kembali ke negara ketiga, seperti Indonesia dan Malaysia, Bangladesh dapat mengurangi tekanan terhadap sumber daya domestik sekaligus berpartisipasi dalam skema burden-sharing global. Artikel ini menegaskan bahwa resettlement bukan semata tindakan kemanusiaan, tetapi strategi kebijakan yang mampu menyeimbangkan antara kepentingan nasional Bangladesh dan prinsip solidaritas internasional dalam tata kelola pengungsi. Kata kunci: Pengungsi Rohingya, Bangladesh, Resettlement, Durable Solution, Kebijakan Pengungsi